Overhead crane dynamics simulation - Lagerev I.A. (Научно-технический вестник Брянского государственного университета)
Overhead crane in normal operation conditions loading simulation methodic and models are present in this article. Simulation results for real overhead crane are received. This research was supported by the grant no. MK-92.2014.8 of the President of Russian Federation for young scientist support.